Game Design Snacks (Play Story Press, 2026)
This is an edited collection of nuggets of game design wisdom. It covers various areas in game design with examples from commercially released videogames. Its goal is to share and raise awareness of excellent game design. The contributing authors are B. Barker, M. Caldwell, J. Grahmann, K. Kotter, L. Neuschwander, T. S. Richard, and J. Zagal.